USING UAVs IN DOCUMENTING CULTRUAL HERITAGE SITES - A CASE STUDY OF ZAKHO HISTORIC CITY IN KURDISTAN REGION, IRAQ - ISMAEL, SHIREEN YOUNUS (Journal of Duhok University, 2021)
In the Kurdistan region, despite an abundance of its cultural heritage sites and lack of majority of these sites for 3D documentation, application of Unmanned Aerial Vehicles (UAVs) for cultural heritage documentation is still in its infancy. 3D Documentation of cultural heritage sites is among the most important initial steps of developing conservation and management plans of any cultural heritage site which necessitates accuracy of the documentation. There is lack of 3D documentation of valuable historic buildings and 3D models of historic areas that help setting guidelines for historic area development in most small cities. In contrast to that, there is a huge of infrastructure building activities carried out in the Kurdistan region since 2005, which is among one of the main reasons that have led to loss of many valuable heritage sites. The choice of documentation technique is always dependent on the site characteristics, the required accuracy, and the main goal of documentation. Nowadays, UAVs have become a staple of documentation technology due to their accuracy, time and cost factors, as well as high abilities. This research describes in detail the activities carried out using UAV for 3D documentation of the Zakho historic area and the Qishla historical building, which are both located in Zakho city, Kurdistan Region of Iraq (KRI). The UAV was used to collect, analyze and manage data using Agisoft Metashape Professional Software to produce point clued, orthomosaic, digital elevation model, and 3D models for the two sites. Finally, this paper discusses the potential of UAVs for cultural heritage site documentation in the context of KRI and how the advantages of this technology be gained before further loss of the richness and details of the cultural heritage sites